(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article presents a study of the concepts of victimology, victimization, victimoligical prevention, and also reveals the reasons for becoming a victim of crime. Analyzed the increased level of victimization in society, which is a weak preventive effect on the victimization of the population. Recommendations are given for preparing a system of victimological prevention measures.